Case report: Brain infarction following percutaneous drainage of a liver abscess post-chemotherapy for pancreatic head cancer - Deng, Wan-qiu; Wei, Bo; Li, Zheng-yan; Liu, Kai (Frontiers in Medicine, 2024)
Bacterial liver abscesses commonly occur in patients with immune deficiencies such as diabetes, post-chemotherapy, or post-immunosuppressive the rapy. The recommended treatment for liver abscesses exceeding 5cm in a diam eter is anti-infection therapy combined with percutaneous catheter drainage. Co mplications may include local spread to adjacent tissues or organs and thromb osis of the liver and portal veins. Rare hematogenous spread to distant sites, s uch as endophthalmitis and central nervous system embolism, have been report ed, though such complications are uncommon post-drainage. This case report d etails a patient who suffered a brain infarction shortly after percutaneous drain age of a large liver abscess.